Some recent advances in ab initio calculations of nonradiative decay rates of point defects in semiconductors. (September 2019) - Wang, Linwang
Abstract: In this short review, we discuss a few recent advances in calculating the nonradiative decay rates for point defects in semiconductors. We briefly review the debates and connections of using different formalisms to calculate the multi-phonon processes. We connect Dr. Huang's formula with Marcus theory formula in the high temperature limit, and point out that Huang's formula provide an analytical expression for the phonon induced electron coupling constant in the Marcus theory formula. We also discussed the validity of 1D formula in dealing with the electron transition processes, and practical ways to correct the anharmonic effects.